2019
DOI: 10.1073/pnas.1901805116
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects for Parkin and LRRK2 in leprosy type-1 reactions and Parkinson’s disease

Abstract: Type-1 reactions (T1R) are pathological inflammatory episodes and main contributors to nerve damage in leprosy. Here, we evaluate the genewise enrichment of rare protein-altering variants in 7 genes where common variants were previously associated with T1R. We selected 474 Vietnamese leprosy patients of which 237 were T1R-affected and 237 were T1R-free matched controls. Genewise enrichment of nonsynonymous variants was tested with both kernel-based (sequence kernel association test [SKAT]) and burden methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 76 publications
2
52
0
Order By: Relevance
“…Parkin and PINK1 have recently been implicated in mitochondria-dependent inflammation, in response to bacterial infection or mitochondrial stress [8][9][10]. Intriguingly, SNPs and missense variants in LRRK2, a gene associated with autosomal dominant PD, have also been linked to susceptibility, inflammatory responses and type-1 reactions in leprosy [12,45,46]. LRRK2 is a large protein of the ROC-COR family of protein kinases, which regulates intracellular trafficking via phosphorylation of Rab GTPases, which are key mediators of pathways implicated in PD [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkin and PINK1 have recently been implicated in mitochondria-dependent inflammation, in response to bacterial infection or mitochondrial stress [8][9][10]. Intriguingly, SNPs and missense variants in LRRK2, a gene associated with autosomal dominant PD, have also been linked to susceptibility, inflammatory responses and type-1 reactions in leprosy [12,45,46]. LRRK2 is a large protein of the ROC-COR family of protein kinases, which regulates intracellular trafficking via phosphorylation of Rab GTPases, which are key mediators of pathways implicated in PD [47].…”
Section: Discussionmentioning
confidence: 99%
“…We extended our analysis to MEIG1, PACRGL, and other axonemal proteins (SPAG16, FAP20, and FAP206), as well as PINK1 and DJ-1, two proteins implicated in PD and which regulate mitochondrial homeostasis [38]. Furthermore, we also included LRRK2, a kinase associated with both leprosy and PD [12]. We found a strong correlation (r = 0.88) between the expression of Parkin and PINK1, with both expressing at very high levels in mitochondria-rich tissues such as muscles and the central nervous system ( Figure 6).…”
Section: Conservation Of the Pacrg-parkin Head-to-head Gene Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The largest association with T1R susceptibility was the rs3761863 SNP previously identified for CD, that encodes the LRRK2 M2397T variant (Fava et al, 2016). However, in a replication study, the same authors demonstrate that the main association between LRRK2 and T1R susceptibility, is actually provided by a protective variant (R1628P) enriched in T1R-free subjects (Fava et al, 2019). Thus, as for PD and IBD, the genetics underlying LRRK2 susceptibility to Leprosy or subsequent complications, likely involves a complex interplay of both risk and protective alleles.…”
Section: Lrrk2 Is Genetically Implicated In Diseasementioning
confidence: 94%
“…Intriguingly, mice with the G2019S LRRK2 mutation showed improved bacterial control of S. typhimurium (Shutinoski et al, 2019), adding to suggestions that some LRRK2 mutations may constitute an evolutionary advantage against infection (Herbst and Gutierrez, 2019). Indeed, LRRK2 kinase activity has also been associated with improved clearance of M. tuberculosis (Hartlova et al, 2018) and protective alleles identified that improve clearance of M. leprae (Fava et al, 2019). However, context again appears to be important with LRRK2 knockout mice showing increased susceptibility to L. monocytogenes (Zhang et al, 2015).…”
Section: Lrrk2 and Pathogen Clearancementioning
confidence: 98%